Metabolomic Analysis of the Urine from Rats with Collagen-Induced Arthritis with the Effective Part of Caulophyllum robustum Maxim. (26th May 2021) - Lü, Shaowa; Zhu, Mingtao; Guo, Qiaoxin; Xu, Dan; Guo, Yuyan; Li, Guoyu; Wang, Qiuhong; Kuang, Haixue
Abstract : Rheumatoid arthritis (RA) is a chronic autoimmune disease with high incidence and high disability and recurrence rates. Caulophyllum robustum Maxim ( C. robustum ) is a traditional Chinese medicine (TCM) with main effective parts (CRME) commonly used for RA treatment. To explore the mechanism of CRME in RA, we used metabolomics to investigate the effect of CRME intervention on urine metabolism in rats with collagen-induced arthritis (CIA). CIA rats were randomly divided into normal control, CIA model, and CRME groups. A metabolomics approach, using Ultra-Performance Liquid Chromatography-Quadrupole-Time-of-Flight/Mass Spectrometry, was developed to perform urinary metabolic profiling. Differential metabolites were identified by comparing the CIA model and CRME groups. Preliminarily, 56 significant differential metabolites were identified in urine, and 20 metabolic pathways were disturbed by the CIA. The amount of 16 different metabolites changed in urine after CRME intervention. The production of these metabolites involves tryptophan, tyrosine, energy, cholesterol, and vitamin metabolism. CRME has anti-inflammatory and immunosuppressive effects in CIA model rats. By examining the endogenous metabolite levels, we identified potential CRME targets and pathways involved in the treatment of RA. The results of our metabolic studies indicate that CRME regulates amino acid, vitamin, energy, and lipid metabolism pathways to treat RA and may provide a new explanation for the anti-RA mechanism of CRME.